2021
DOI: 10.1007/s11259-021-09827-x
|View full text |Cite
|
Sign up to set email alerts
|

Aluminosilicates at different levels in rye litter and feed affect the growth and meat quality of broiler chickens

Abstract: Litter sanitation treatments and feed supplements that stimulate bird growth. The aim of this study was to analyse the effects of zeolite (z) and halloysite (h) in feed and rye straw litter on growth performance, meat quality in chickens. 500 males Ross 308 were allocated to 5 groups (10 replicates). Feed for groups 2–5 was supplemented with halloysite and zeolite (25:75). The content of aluminosilicates in the feed was different depending on the feeding phase: 0.5, 1, 1.5, or 2%. The following doses were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The significant superiority in live body weight and weight gain of T3 (adding zeolite by ⅓ kg of the litter weight) and T4 (Adding zeolite by ⅔ kg of the litter weight) compared to control treatment may be due to use zeolite, as filter which increases the amount of absorbed air and thus reduces the humidity of the air surrounding the bird, which provides a suitable environment for growth and reduces ammonia release, and has a positive impact on the bird's health condition due to increase in live body weight and weight gain [25,26]. These results agreed with [27] who found adding zeolite to the litter at concentrations of 400, 800, and (600) g/m respectively, caused a significant superiority in weight gain compared to control treatment. Table 2.…”
Section: Live Body Weight and Weight Gainsupporting
confidence: 75%
“…The significant superiority in live body weight and weight gain of T3 (adding zeolite by ⅓ kg of the litter weight) and T4 (Adding zeolite by ⅔ kg of the litter weight) compared to control treatment may be due to use zeolite, as filter which increases the amount of absorbed air and thus reduces the humidity of the air surrounding the bird, which provides a suitable environment for growth and reduces ammonia release, and has a positive impact on the bird's health condition due to increase in live body weight and weight gain [25,26]. These results agreed with [27] who found adding zeolite to the litter at concentrations of 400, 800, and (600) g/m respectively, caused a significant superiority in weight gain compared to control treatment. Table 2.…”
Section: Live Body Weight and Weight Gainsupporting
confidence: 75%
“…Using zeolite and halloysite 0.5–2% in the feed, with the simultaneous addition of aluminosilicates to the rye litter at 800 g/m 2 (with different proportions), resulted in higher BW and BWG of broiler chickens. However, FI increased in some groups 28 . In rearing chickens, the aluminosilicates mentioned above were used in various configurations, also for bedding in the form of wheat pellets 29 .…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies on using aluminosilicates in poultry production confirmed their effect as a feed or bedding additive on production results, slaughter yield, meat quality, and intestinal morphology ( Banaszak et al, 2020 , 2021a , 2022b ; Biesek et al, 2021a ). Aluminosilicates also affect the expression of intestinal mucosa genes in the context of supporting health status ( Biesek et al, 2021b ; Dunislawska et al, 2022 ).…”
Section: Pathways Of Immunostimulation and Immunomodulationmentioning
confidence: 86%
“…The addition of zeolite and halloysite to the feed at the level of 0.5 to 2% and bedding (800 g/m 2 surface, in various proportions) had a beneficial effect on BWG and FI, as well as on the qualitative characteristics of the breast muscles (water absorption, proteins) ( Banaszak et al, 2022a ). The authors suggested using aluminosilicates in production due to their beneficial effects ( Banaszak et al, 2021a , b , 2022b ). The cited studies focused on the production results of broiler chickens.…”
Section: Pathways Of Immunostimulation and Immunomodulationmentioning
confidence: 99%